Produtividade do capim bermuda em consorciado com leguminosas de ciclo hibernal - Anjos, Amanda Nunes Assis dos (2015)
The objective of this research was to evaluate three grazing systems with Coastcross-1 (CC) + 100 kg N/ha/year + common vetch; CC + 100 kg N/ha/year + arrowleaf clover; and CC + 200 kg N/ha/year. The experiment was carried out from May 2013 to April 2014. Lactating Holstein cows were used in the evaluation. The grazing method was the rotative stocking, with one day of occupation. Thirteen grazing cycles were performed during the experimental period (313 days). The forage mass, botanical composition, leaf/stem ratio; daily accumulation rate, production and forage intake; grazing efficiency and stocking rate were evaluated. Experimental design was completely randomized with three treatments (grazing systems), three replicates (paddocks) in completely split-plot time (seasons). The average of forage production and stocking rate were 20.8, 17.6 and 19.7 t/ha/year; 7.0, 6.8 e 6.8 animal units/ha/day, respectively. Better results were found on CC + 100 kg of N/ha + common vech and CC + 200 kg of N/ha pasture systems. The presence of the legumes did not affect the structural composition of Coastcross-1, but implies delay in the development of this grass.